English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
1

3x + 2y=10
6x=5x+26
how do you solve this solution

2007-02-07 04:55:36 · 9 answers · asked by Anonymous in Science & Mathematics Mathematics

9 answers

solve for x in the second equation

6x=5x+26
x=26

plug in 26 for x in the first equation:

3(26) + 2y = 10
2y = 10 - 78
2y = -68
y= -34

2007-02-07 05:04:01 · answer #1 · answered by Anonymous · 0 0

i imagine you do it this way: in case you do like MINUS 3x on the single aspect you should do an same element on the different aspect. So 2y=10-3x Then flow all that´s on the right to the left to get 0 on the right aspect. 2y + 3 x - 10 = 0 and that is a "secon-degree equation" Sorry ´bout my english, i imagine you understood besides...:-)

2016-11-25 23:50:01 · answer #2 · answered by ? 4 · 0 0

6x = 5x +26

<=> x = 26 -- subtracting 5x from both sides

Plug this into first equation

3*26 +2y = 10
78 +2y = 10
2y = -68
y = -34

2007-02-07 05:04:24 · answer #3 · answered by Kirstin 2 · 0 0

3x+2y=10 6x=5x+26
3x+2y=10 6x-5x=5x-5x+26
3x+2y=10 x=26

Then, go back to the original equation and substitute in x to find y.
3(26)+2y=10
78+2y=10
78-78+2y=10-78
2y=-68
2y/2=-68/2
y=-34

Solution (26,-34)

2007-02-07 05:40:57 · answer #4 · answered by Ashley 2 · 0 0

if 6x = 5x + 26, then x = 26

3(26) + 2y = 10

78 + 2y = 10

10 - 78 = -68

2y = -68

-68/2 = -34

y = -34

2007-02-07 05:04:00 · answer #5 · answered by jttoledo9279@sbcglobal.net 1 · 0 0

6x = 5x + 26
therfore x = 26
putting the value of x in first equation
we get y = -34.

then plug x = 26 and y = 34 in the first equation and check that it comes to 10.
same with second equation..

2007-02-07 05:03:32 · answer #6 · answered by javaman 1 · 0 0

The second one is right, here is what you do. You have to get the X's to one side preferably the side opposite of 26. to do that you have to subtract 5X from 5X. leaving you with just the 26. then you have to subtract the 5X from the 6X. that will leave you with the answer literally. because 1X is X. so it would be X=26. The first one though I really cant remember how to do.

2007-02-07 05:14:42 · answer #7 · answered by crutchduck 3 · 0 1

as you have written it, x=26

therefore

78+2y=10

y=-34

(26,-34)

if you had written it meaning 6y=5x+26, then

y=3/2x+5
y=5/6x+13/3

3/2x+5=5/6x+13/3 or

9x+30=5x+26
4x=-4
x=-1

therefore,

3*-1+2y=10

y=13/2

the answer is,
(-1,13/2)

2007-02-07 05:02:20 · answer #8 · answered by Anonymous · 1 0

I think you have mistyped the question. Cross check it again and then email it to me. I will get you the soloution for sure. There seems some mistake with second equtation

2007-02-07 05:00:39 · answer #9 · answered by Anonymous 2 · 0 0

fedest.com, questions and answers